Integrated analysis of Tinospora cordifolia germplasm: Nutritional, qualitative, quantitative, and phytochemical traits: Integrated analysis of Tinospora - Akhilraj, B C; Suresh, J; Rajamani, K; Kumar, M; Gnanam, R (Journal of Spices and Aromatic Crops, 2025)
Tinospora cordifolia, often known as "Guduchi" is a deciduous climber and is considered valuable in terms of its immense medicinal properties. This study evaluated 48 Tinospora cordifolia germplasm accessions collected from Tamil Nadu for their nutritional, qualitative, quantitative, and phytochemical properties. Significant variations were observed among the accessions. TC-22 exhibited the highest phenol content (122.73 mg/g) and flavonoid content (18.84 mg/g), while TC-30 recorded the highest tannin content (234.56 mg/g). TC-20 demonstrated superior protein (13.85%), carbohydrate (86.92 mg/g), and antioxidant activity (261.74%) levels. Additionally, TC-20 displayed elevated potassium (1.45%), calcium (0.35%), and iron (48.74%) levels, with the highest zinc content (15.67 μg/g) among accessions. TC-30 had the highest fat content (8.81%), while TC-22 recorded the maximum cardiac glycosides (2.27%). The study identified TC-35 as having the highest fiber content (13.22%) and energy value (99.66 Kcal/100g). Vitamin C (68.96 mg/100g) and vitamin A (0.44 mg/100g) were most abundant in TC-33. These findings provide valuable insights into the biochemical diversity of T. cordifolia germplasm, highlighting its potential for nutritional and therapeutic applications. Findings unmistakably demonstrated the significance of ecological condition variables in determining the quantitative and qualitative parameters of diverse accessions from the different places of Tamil Nadu.